Do LBO Supermarkets Charge More? An Empirical Analysis of the Effects of LBOs on Supermarket Pricing - Chevalier, Judith A. (Journal of Finance, 1995)
This article examines changes in supermarket prices in local markets following supermarket leveraged buyouts (LBOs). I find that prices rise following LBOs in local markets in which the LBO firm's rivals are also highly leveraged and that LBO firms have higher prices than their less leveraged rivals, suggesting that LBOs create incentives to raise prices. However, I also find that prices fall following LBOs in local markets in which rival firms have low leverage and are concentrated. These price drops are associated with LBO firms exiting the local market, suggesting that rivals attempt to “prey” on LBO chains.